Silicon Enhances Water Stress Tolerance by Improving Root Hydraulic Conductance in Solanum lycopersicum L. - Shi, Yu; Zhang, Yi; Han, Weihua; Feng, Ru; Hu, Yanhong; Guo, Jia; Gong, Haijun (Frontiers in Plant Science, 2016)
Silicon (Si) can improve drought tolerance in plants, but the mechanism is still not fully understood. Previous research has been concentrating on Si’s role in leaf water maintenance in Si accumulators, while little information is available on its role in water uptake and in less Si-accumulating plants. Here, we investigated the effects of Si on root water uptake and its role in decreasing oxidative damage in relation to root hydraulic conductance in tomato (Solanum lycopersicum ‘Zhongza No.9’) under water stress. Tomato seedlings were subjected to water stress induced by 10% (w/v) polyethylene glycol-6000 in the absence or presence of 2.5 mM added silicate. The results showed that Si addition ameliorated the inhibition in tomato growth and photosynthesis, and improved water status under water stress. The root hydraulic conductance of tomato plants was decreased under water stress, and it was significantly increased by added Si. There was no significant contribution of osmotic adjustment in Si-enhanced root water uptake under water stress. The transcriptions of plasma membrane aquaporin genes were not obviously changed by Si under water stress. Water stress increased the production of reactive oxygen species and induced oxidative damage, while added Si reversed these. In addition, Si addition increased the activities of superoxide dismutase and catalase and the levels of ascorbic acid and glutathione in the roots under stress. It is concluded that Si enhances the water stress tolerance via enhancing root hydraulic conductance and water uptake in tomato plants. Si-mediated decrease in membrane oxidative damage may have contributed to the enhanced root hydraulic conductance.